Cerebral Venous Sinus Thrombosis After Translabyrinthine Vestibular Schwannoma—A Prospective Study and Suggested Management Paradigm. Issue 2 (February 2020) - Guazzo, Emily; Panizza, Benedict; Lomas, Andrew; Wood, Martin; Amato, Damien; Alalade, Andrew; Gandhi, Mitesh; Bowman, James
Abstract : Objective: To prospectively evaluate the incidence, risk factors and natural history of postoperative cerebral venous sinus thrombosis (pCVST) in translabyrinthine vestibular schwannoma microsurgical resection and propose a potential management paradigm. Study Design: Prospective, single cohort, multicenter study. Setting: State-wide academic tertiary referral centers. Patients: Fifty-four consecutive patients who underwent translabyrinthine vestibular schwannoma resection. Main Outcome Measures: Incidence of pCVST on postoperative imaging on Day 7, Day 28, and 12 months postoperatively. Patients and tumor characteristics, risk factors, length of stay, intraoperative parameters, complications, and follow-up were analyzed. Results: pCVST was demonstrated in 21 patients (38.9%) on postoperative imaging. All patients with pCVST were treated conservatively and remained asymptomatic in the immediate postoperative period and long-term follow-up. There were no instances of venous infarction, intracranial hemorrhage, or neurological deficits. A majority (61.1%) of pCVST recannalised on long-term follow up with conservative management. There was a statistical association with pCVST and surgery on the side of the non-dominant cerebral venous drainage (n = 17, 80.1%, p = 0.034). Patients with pCVST were significantly more likely to have a postoperative cerebrospinal fluid (CSF) leak (n = 5, 23.8%, p = 0.017). Conclusion: The incidence of pCVST following translabyrinthine vestibular schwannoma resection is much higher than previously recognized. pCVST is more likely to occur when surgery is performed on tumors situated on the side of non-dominant cerebral venous drainage. Despite the high prevalence of this iatrogenic phenomenon, all patients were asymptomatic and a majority resolved, thereby suggesting that conservative management is safe. Correlation between pCVST and increased incidence of CSF leak requires further investigation.